O Manto Sagrado e o preconceito velado: o estigma negativo em torno da torcida do Flamengo à luz da Historiografia - ALVES, Gabriel Ribeiro (2024)
This article analyzes the stigma associated with Flamengo fans, who are often labeled by the press and society as "favela fans." Over the years, this labeling has influenced public perception and shaped narratives that reflect and perpetuate socioeconomic and cultural stigmas. The research focuses on media coverage and how it has addressed the social composition and characteristics of Flamengo fans, considered one of the largest and most diverse in Brazil. Through a historical analysis, the study seeks to understand how media discourse contributed to the formation of this stigma and what social and cultural impacts this has generated over time. The methodology combines both qualitative and quantitative analyses, investigating printed and digital materials that document the representation of Flamengo fans in both the press and popular culture. A major question to ask in order to understand the debate is: why is the most popular club in the country, which plays in the most popular sport in the country, so stigmatized by people who are not fans in general? By exploring the narratives that emerge in these contexts and how they relate to social and cultural dynamics, the article aims to broaden the discussion on the complex relationships between football, media and society, as well as their impact on the construction of identities and inequalities.